Persistent neurological manifestations in long COVID-19 syndrome: A systematic review and meta-analysis - Rizaldy Taslim Pinzon; Vincent Ongko Wijaya; Abraham Al Jody; Patrick Nalla Nunsio; Ranbebasa Bijak Buana (Elsevier, 2022)
Background: Several studies have reported prolonged symptoms especially neurological symptoms following acute infection in patients with COVID-19, known as long COVID-19. There are only few studies investigating this population and relatively less known, including nervous system involvement. A systematic review and meta-analysis of these studies are required to understanding the prevalence of persistent neurological manifestations after COVID-19. Objective: To conduct a systematic review and meta-analysis on the persistent neurological manifestations in COVID-19 survivors. Methods: Authors conducted a literature search through PubMed and MedRxiv from January 1st, 2020 to October 2021 according to PRISMA guideline. Furthermore, the authors added additional sources by reviewing related references. Studies presenting the neurologic features of long COVID-19 patients in their data were included. Case reports and case series also included in this review. The quality of the studies was assessed based on the Oxford Centre for Evidence-Based Medicine guidelines. Selected studies were included in the meta-analysis of proportion and heterogeneity test. Findings: From 128 identified studies, 36 were eligible, with 9944 participants included. Most of the included studies had mean duration of follow-up after COVID-19 onset of less than 6 months. Fatigue was the most common (52.8%, 95%CI 19.9 - 84.4) symptoms of long COVID, followed by cognitive disorder (35.4%, 95%CI 2.1 - 81.7); paresthesia (33.3%, 95%CI 2.7 - 76.6); sleep disorder (32.9%, 95%CI 6.5 - 67.4); musculoskeletal pain (27.8%, 95%CI 12.7 - 46); and dizziness (26.4%, 95%CI 4.6 - 57.9). Conclusion: Neurological manifestations are prevalent and persisting in patients with long COVID. The duration of the symptoms are vary among literatures. However, the frequency are mostly observed during the first six months after the illness onset.